Exploring the multifaceted potential of (R)-ketamine beyond antidepressant applications - Zhang, Senbing; Pu, Yanzhu; Liu, Jianning; Li, Lewen; An, Chibing; Wu, Yumin; Zhang, Wenjie; Zhang, Wenxia; Qu, Song; Yan, Wenjun (Frontiers in Pharmacology, 2024)
(R, S)-and (S)-ketamine have made significant progress in the treatment of treatment-resistant depression (TRD) and have become a research focus in recent years. However, they both have risks of psychomimetic effects, dissociative effects, and abuse liability, which limit their clinical use. Recent preclinical and clinical studies have shown that (R)-ketamine has a more efficient and lasting antidepressant effect with fewer side effects compared to (R, S)-and (S)-ketamine. However, a recent small-sample randomized controlled trial found that although (R)-ketamine has a lower incidence of adverse reactions in adult TRD treatment, its antidepressant efficacy is not superior to the placebo group, indicating its antidepressant advantage still needs further verification and clarification. Moreover, an increasing body of research suggests that (R)-ketamine might also have significant applications in the prevention and treatment of medical fields or diseases such as cognitive disorders, perioperative anesthesia, ischemic stroke, Parkinson's disease, multiple sclerosis, osteoporosis, substance use disorders, inflammatory diseases, COVID-19, and organophosphate poisoning. This article briefly reviews the mechanism of action and research on antidepressants related to (R)ketamine, fully revealing its application potential and development prospects, and providing some references and assistance for subsequent expanded research.